Tabebuia roseoalba: In Vivo Hypouricemic and Anti-inflammatory Effects of Its Ethanolic Extract and Constituents - Ferraz-Filha, Zilma Schimith; Michel Araújo, Marcela Carolina de Paula; Ferrari, Fernanda Cristina; Dutra, Iális Paiva Andrade Rodrigues; Saúde-Guimarães, Dênia Antunes (Planta Medica, 2016)
Tabebuia species have several uses in folk medicine, including their use to treat inflammation and rheumatism. The aim of this study was to investigate whether the ethanolic extract of leaves from Tabebuia roseoalba and isolated compounds could be useful to decrease serum uric acid levels and restrain the gout inflammatory process. The compounds α-amyrin, β-amyrin, sitosterol, and stigmasterol were isolated from the ethanolic extract. Rutin and caffeic acid were identified in the ethanolic extract by HPLC analysis. The anti-hyperuricemic effect, liver xanthine oxidoreductase inhibition, and anti-inflammatory activity of the ethanolic extract and isolated compounds were evaluated on hyperuricemic mice and on paw edema induced by monosodium urate crystals in mice. The ethanolic extract of leaves from T. roseoalba, β-amyrin, and stigmasterol were able to reduce serum uric acid levels in hyperuricemic mice through inhibition of liver xanthine oxidase activity and significantly decreased the paw edema induced by monosodium urate crystals. The antioxidant activity of the ethanolic extract and its ability to inhibit xanthine oxidase were also evaluated in vitro. The ethanolic extract of leaves from T. roseoalba showed significant antioxidant activity in the three evaluated assays. Results were analyzed using GraphPad Prism 5.01. One-way ANOVA followed by Studentʼs Newman-Keulʼs test was used to determine the significant differences between groups. The results show that the ethanolic extract of leaves from T. roseoalba, β-amyrin, and stigmasterol can be promising agents for the treatment for gouty arthritis, hyperuricemia, and inflammation. Stigmasterol, β-amyrin, and rutin contribute to the observed effects of the ethanolic extract of leaves from T. roseoalba.
Keywords: Tabebuia roseoalba; Bignoniaceae; gout; inflammation; hyperuricemia; antioxidant